Optical networking standards A Comprehensive Guide for Professionals - Kazi, Khurram (Springer US, 2006)
Optical Networking Standards: A Comprehensive Guide for Professionals provides a single source reference of over a hundred standards and industry technical specifications for optical networks at all levels: from components to networking systems through global networks, as well as coverage of networks management and services. This book focuses on the recently approved, adopted and implemented standards that have fueled the development of versatile switches, routers and multi-service provisioning platforms. These networking elements have enabled the service-providers world-wide to offer flexible yet customized bundled-services based on IP, MPLS and Carrier-Grade Ethernet. Highlights include recent advancements involving: - Critical technical standards and implementation from ITU-T, IETF, MEF, and OIF - Optimization of SONET/SDH and OTN infrastructure for data delivery, GFP, VCAT and LCAS - IP, MPLS, Ethernet and Fibre Channel services over public networks - Optical control plane for dynamically switched optical networks, ASON - Network survivability and recovery - Timing in global optical networks - Architecture of optical transport networks - Network element design using standardized components and inter-components communication - Numerous illustrative examples showing actual situations or cases implemented Lead implementers, contributors and editors of the new standards from networking equipment and VLSI manufacturers and service providers such as AMCC, Agere Systems, British Telecom, Ciena Corporation, Cisco Systems, Lucent Technologies, Marconi, Nortel, Tellabs, PMC-Sierra, Strix Systems and other independent consultants have come together to produce this uniform and complete reference. The volume has been edited by Dr. Khurram Kazi, a networking veteran with over 19 years of real-world expertise in architecting and designing ASICs and systems for SONET, IP, ATM, PDH and Ethernet networks. Dr. Kazi has published refereed articles and conference tutoria